A systematic review of the association between obesity and asthma in children - Liu, Pei-Ching (2013)
AIMS: To provide a comprehensive integration of contemporary studies focusing on the relationship between obesity and asthma in paediatric populations. BACKGROUND: The simultaneous increase in asthma and obesity prevalence has been widely discussed over the past twenty years. Although studies have discovered a positive correlation between the two, evidence-based findings are needed to develop nursing interventions. DATA SOURCES: An electronic database search was conducted for studies published between January 1966 - May 2011. Additional articles were identified through the reference lists of reviewed papers. REVIEW METHODS: A quantitative systematic review was undertaken to aggregate evidence regarding the association between obesity and asthma in children. Inclusion/exclusion criteria and quality appraisal were applied to ensure research primarily designed to study the relationship between obesity and asthma in children was included. RESULTS: The majority of studies support a positive association between obesity and asthma in children. Among correlates recognized as important effect modifiers, gender was the most prominent, with obese girls more likely to have asthma diagnoses than obese boys. Scrutinization of covariates in selected studies revealed that most related to children's demographic characteristics and were inconsistent across the studies. CONCLUSIONS: This review was designed to integrate contemporary scientific findings on the association between obesity and asthma by including a large number of studies with variant research designs. To identify high-risk groups and develop nursing interventions to help children affected by both epidemics, more interdisciplinary and well-designed investigations focusing on an expanded spectrum of correlates including demographic and behavioural factors are warranted.